Can the sustainable development goals for cancer be met in Brazil? A population-based study - De Camargo Cancela, Marianna; Bezerra de Souza, Dyego Leandro; Leite Martins, Luís Felipe; Borges, Leonardo; Schilithz, Arthur Orlando; Hanly, Paul; Sharp, Linda; Pearce, Alison; Soejomataram, Isabelle (Frontiers in Oncology, 2023)
Background: A one-third reduction in premature mortality (30-69 years) from chronic noncommunicable diseases is goal 3.4 of the United Nations Sustainable Development Goals (UN SDG). The burden of NCDs is expected to continue to increase in low- and middle-income countries, including Brazil. Objectives: The aim of this study was to assess geographical and temporal patterns in premature cancer mortality in Brazil between 2001 and 2015 and to predict this to 2030 in order to benchmark against the 3.4 SDG target. Methods: We used data on deaths from cancer in those aged 30-69, by age group, sex and cancer site, between 2001 and 2015 from the National Mortality Information System of Brazil (SIM). After correcting for ill-defined causes, crude and world age-standardised mortality rates per 100,000 inhabitants were calculated nationally and for the 5 regions. Predictions were calculated using NordPred, up to 2030. Results: The difference in observed (2011-2015) and predicted (2026-2030) mortality was compared against the SDG 3.4 target. Between 2011-2015 and 2026-2030 a 12.0% reduction in premature cancer age-standardised mortality rate among males and 4.6% reduction among females is predicted nationally. Across regions this varied from 2.8% among females in North region to 14.7% among males in South region. Lung cancer mortality rates are predicted to decrease among males but not among females nationally (men 28 %, females 1.1% increase) and in all regions. Cervical cancer mortality rates are projected to remain very high in the North. Colorectal cancer mortality rates will increase for both sexes in all regions except the Southeast. Conclusions and recommendation: Cancer premature mortality is expected to decrease in Brazil, but the extent of the decrease will be far from the SDG 3.4 target. Nationally, only male lung cancer will be close to reaching the SDG 3.4 target, reflecting the government’s long-term efforts to reduce tobacco consumption. Projected colorectal cancer mortality increases likely reflect the epidemiological transition. This and, cervical cancer control will continue to be major challenges. These results will help inform strategic planning for cancer primary prevention, early detection and treatment programs; such initiatives should take cognizance of the regional differences highlighted here.